Fluctuaciones biocenóticas y relictos herpetológicos de la planicie de Lonco-Luán (Neuquén) - Cei, José Miguel Alfredo María (1970)
The ecological features of the Loneo-Luán plateau (Neuquén) are reported. Sympatry of Telmatobius montanus, Pleurodema bibroni ( = thaul), and Pleurodema bufonina is pointed out, together with a general discussion of the late Tertiary and Quaternary events on the Loneo- Luán volcanic highlands.